2023
DOI: 10.1364/oe.489720
|View full text |Cite
|
Sign up to set email alerts
|

Study on the radiation and self-absorption characteristics of plasma under various background gases

Abstract: The self-absorption effect is a primary factor responsible for the decline in the precision of quantitative analysis techniques using plasma emission spectroscopy, such as laser-induced breakdown spectroscopy (LIBS). In this study, based on the thermal ablation and hydrodynamics models, the radiation characteristics and self-absorption of laser-induced plasmas under different background gases were theoretically simulated and experimentally verified to investigate ways of weakening the self-absorption effect in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Their findings suggest that the attenuation of self-absorption manifests as apparent when helium is used as the ambient gas. Wang et al 102 simulated and verified the radiation characteristics and selfabsorption effect of laser-induced plasmas under different background gases. They found that the self-absorption effect can be alleviated by utilizing a gas with a low ionization potential.…”
Section: Experimental Parametersmentioning
confidence: 99%
“…Their findings suggest that the attenuation of self-absorption manifests as apparent when helium is used as the ambient gas. Wang et al 102 simulated and verified the radiation characteristics and selfabsorption effect of laser-induced plasmas under different background gases. They found that the self-absorption effect can be alleviated by utilizing a gas with a low ionization potential.…”
Section: Experimental Parametersmentioning
confidence: 99%
“…Rezaei et al used calibration curves and growth curves to discuss the influence of He gas on the self-absorption of spectral lines (Cu I 324.75 nm and Cu I 327.40 nm) at different air pressures; the results of both methods showed that the self-absorption increased with the air pressure [14]. Wang et al found that the self-absorption of atomic spectral lines (Mg and Al) increased with decreasing ambient pressure [15]. Rezaei et al studied the self-absorption of spectral lines (Al) by comparing the spectral intensities with and without self-absorption in Ar and He gas environments at atmospheric pressure [16].…”
Section: Introductionmentioning
confidence: 99%